Left atrial size and contractile function in healthy dogs and dogs with chronic mitral valve disease - Petrus,Lilian C. (2018)
ABSTRACT: In humans, left atrial enlargement and reduced contractile functions are associated with adverse cardiovascular events and a poor prognosis in many dilatation of the left atrium occurs with the gradual evolution of chronic mitral valve disease and is well diseases. The left atrium is the most compromised cardiac chamber in dogs with chronic mitral valve disease (CMVD). Therefore, this study aimed to compare the main parameters of left atrial enlargement (left atrium/aorta ratio, left atrial diameter and volume indices) and contractile function (transmitral flow peak velocity A wave and time velocity integral, atrial fraction, and atrial ejection force) at different stages of valve disease, and correlate the left atrial diameter, volume, and contractile function indices with echocardiographic variables predictive of heart failure in dogs (transmitral flow peak velocity E wave, E wave/IVRT ratio, E wave/E´wave ratio, and E wave/A wave ratio). The results showed that progressive characterized by the left atrium/aorta ratio and left atrium volume index. The left atrial diameter and volume indices and left atrium/aorta ratio correlated positively with the transmitral flow peak velocity E wave and E wave/IVRT ratio, which are important indices of diastolic function. The left atrial contractile function indices increased as CMVD evolved. Except for the atrial fraction, the left atrial contractile function indices correlated with the left ventricular filling pressure indices.